External Beam Radiation Therapy in Treatment of Malignant Pheochromocytoma and Paraganglioma - Vogel, Jennifer (Frontiers Media S.A., 2014)
Purpose: Pheochromocytomas (PCCs) are neuroendocrine tumors arising from the adrenal medulla or as paraganglioma (PGL) from extra-adrenal sites. While usually benign, a small fraction is malignant. Multi-modality therapy is used in treating malignant disease; however, little data exist on the role of external beam radiation therapy (EBRT). In this retrospective review, we assessed response to EBRT in malignant PCCs or PGLs. Methods and Materials: Records of patients treated at the National Institutes of Health who received EBRT between 1990 and 2012 were studied. Patients were assessed for symptomatic control, biochemical response, local and distant control by response evaluation criteria in solid tumors v1.1 or stable disease on imaging reports, toxicity by radiation therapy oncology group (RTOG) criteria, and survival. Results: There were 24 patients treated who received EBRT to lesions of the abdomen (n = 3), central nervous system (n = 4), and bone (n = 40). Lesions were treated with 3D conformal EBRT to a mean dose of 31.8 Gy in 3.3 Gy fractions, or fractionated stereotactic radiosurgery to 21.9 Gy in 13.6 Gy fractions. Patients experienced acute (n = 15) and late (n = 2) RTOG toxicities; no patient experienced acute toxicity ≥4 or late toxicity ≥2. Symptomatic control was achieved in 81.1% of lesions. Stable radiographic response was achieved in 86.7% of lesions with progression in 13%. Distant progression was observed overall in 75% of patients and average survival was 52.4 months. Conclusion: Malignant PCC and PGL often do not respond well to current systemic therapies. In these cases, EBRT can be considered in patients with symptomatic, localized disease progression.